New Trends in Economic Globalization - Gurgu, Elena; Cociuban, Aristide (Journal of Economic Development, Environment and People, 2016)
The long disputed and analyzed, globalization has now become an objective phenomenon unprecedented in world history, as magnitude and evolution. Criticized by some, revered by others, it seems that follows its trajectory. For us relevant are some negative aspects of globalization, but more significant are those that maintain balance and well-being of mankind. Based on the research conducted we have concluded that both globalization and regionalization emerged and developed as a result of unprecedented increased competition in the level of trade of states or regions.